An Estimate of the Tensile Strength Based on P-Wave Velocity and Schmidt Hardness Rebound Number - Hosseini, Mehdi; Shirin, Danial (International Journal of Geography and Geology, 2014)
Tunnels, roads, bridges, dams, power plants, etc., are constructed in rock formation. Various rock parameters are important for the design of these structures such as compressive and tensile strengths of the embedded rocks. Preparation of samples and performing uniaxial and Brazilian tensile tests require a lot of time and money; and they are not operable in all samples. Therefore, much easier and less costly methods are used to determine tensile strength. Schmidt hammer and sound velocity tests are among these simple and inexpensive tests. Another advantage of these tests is that they are non-destructive and operable in the deserts. The main objective of this study was to obtain the relationship between the sound velocity, the Schmidt hammer rebound number and the tensile strength. This study was conducted on samples of sandstone, tuff, marble, limestone, red sandstone and marl. Simple and multivariate regression models were used to obtain this relationship. Root Mean Square Error (RMSE) and value account for (VAF) were determined to control the performance of provided equations. These two indices were equal to 2.20 and 46.5 in the relation between the sound velocity and the tensile strength; and they were equal to 0.09 and 81.49 in the relation between the Schmidt hardness rebound number and the tensile strength when the simple regression analysis was used, while they were equal to 0.24 and 80.91 when multivariate regression analysis.